Constructing and applying an exercise counseling model for pregnant women: A preliminary study. (November 2018) - Lee, Ching-Fang; Huang, Yao-Chung; Chi, Li-Kang; Lin, Hsien-Ming; Lin, Chen-Ju; Hsiao, Sheng-Mou
Abstract: Pregnant women tend to exercise less than women who have not yet been pregnant. In the present study, which involves two studies, we aimed to construct an effective, individualized exercise counseling model for pregnant women. In study 1, a three-round session that involved 10 multidisciplinary health care experts reached a consensus via the Delphi method. In the preliminary study, two healthy pregnant women were recruited from the prenatal outpatient departments of hospitals in Taipei, Taiwan. Both of them were 32 years old and primipara. The results of study 1, the established five stages of the individualized exercise counseling model for pregnant women were as follows: assessment, defining barriers that interfere with achieving the target, planning, implementation and monitoring, and evaluation. In the preliminary study, we applied this counseling model of study 1 to 2 healthy pregnant women. The 5-stage counseling model can encourage pregnant women to begin to exercise or to continue exercising. We believe that this exercise counseling model can potentially be used by nurses. It can help them to encourage pregnant women to regularly exercise, and to promote exercise as part of a healthy lifestyle. Highlights: The five stages of the Exercise Counseling Model for pregnant women are assessment, defining barriers, planning, implementation and monitoring, and evaluation. The counseling model provides to be effective in encouraging pregnant women to begin to exercise or to continue exercising. This exercise counseling model can provide guidelines for health care staff members to follow in their practice of encouraging women to exercise during pregnancy.